Studi Kasus Kepemimpinan Kepala Sekolah Terhadap Literasi Siswa Sekolah Dasar - Prapti, Suprapti; Darmuki, Agus; Surachmi, Sri (Trihayu: Jurnal Pendidikan Ke-SD-an, 2024)
This research delves into the leadership strategies employed by the principal of SD Negeri 3 Suru to enhance literacy activities within the school. Utilizing a qualitative case study approach, interviews and documentation reveal various initiatives implemented by the principal, such as the "Sweet Thursday Movement" and scheduled reading time. The principal's active involvement in managing and monitoring the program, coupled with the positive support from teachers, serve as key driving factors. Resource constraints did not hinder the program's positive impact on students' literacy skills. Regular evaluations ensure continuous improvement. These findings underscore the crucial role of the principal's leadership in fostering a literacy culture at SD Negeri 3 Suru. Targeted policies, the principal's active role, collaboration with teachers, and ongoing evaluation are key to the program's success. This research provides a foundation for other schools to develop effective literacy programs, emphasizing the importance of leadership in cultivating a strong literacy culture.